2017
DOI: 10.1002/nbm.3785
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion MRI fiber tractography of the brain

Abstract: The ability of fiber tractography to delineate non-invasively the white matter fiber pathways of the brain raises possibilities for clinical applications and offers enormous potential for neuroscience. In the last decade, fiber tracking has become the method of choice to investigate quantitative MRI parameters in specific bundles of white matter. For neurosurgeons, it is quickly becoming an invaluable tool for the planning of surgery, allowing for visualization and localization of important white matter pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
354
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 440 publications
(387 citation statements)
references
References 121 publications
(277 reference statements)
3
354
0
4
Order By: Relevance
“…This limited variability in individual SC matrices could be due to the quality of current individual SC matrices. Although great advances have been made in diffusion-weighted imaging acquisitions and tractography algorithms, it is known that DWI tractography underestimates the number of short-distance streamlines in favor of long fiber tracks (Jeurissen et al, 2017). Although in the current study we have used a relatively new multi-shell DWI sequence with b-values of up to 2800 s/mm 2 and a state-of-the-art processing pipeline, future studies could investigate whether prediction accuracies of individual SC matrices improve when using data of even better quality (using for example 7T MRI scanners, with multiband sequences and/or longer acquisition times).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This limited variability in individual SC matrices could be due to the quality of current individual SC matrices. Although great advances have been made in diffusion-weighted imaging acquisitions and tractography algorithms, it is known that DWI tractography underestimates the number of short-distance streamlines in favor of long fiber tracks (Jeurissen et al, 2017). Although in the current study we have used a relatively new multi-shell DWI sequence with b-values of up to 2800 s/mm 2 and a state-of-the-art processing pipeline, future studies could investigate whether prediction accuracies of individual SC matrices improve when using data of even better quality (using for example 7T MRI scanners, with multiband sequences and/or longer acquisition times).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a distance matrix was constructed by calculating the average length of all streamlines connecting any two nodes (MRtrix3 tck2connectome). By using a proper high-order model and taking into account the full fiber orientation distribution function (through CSD), by taking into account the presence of non–white matter tissue (through multi-tissue CSD), by applying realistic individual anatomic priors (through ACT), and by ensuring fidelity of the tractograms to the data (through SIFT), it has been shown that the biological accuracy of tractograms can be vastly increased compared with those obtained with unfiltered unconstrained diffusion tensor tracking (Jeurissen et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…However, although empirical or simulation studies can clearly demonstrate that variation in these tissue properties modulates diffusion parameters, we are still faced with an inverse problem when trying to interpret an observed difference in diffusion parameters (e.g. reduced FA), as there is no one‐to‐one relationship between a given diffusion parameter and the underlying tissue structure . Nevertheless, diffusion parameters provide useful non‐invasive measures of local tissue microstructure, with sensitivity to features including membrane integrity, myelin thickness, axon diameter and packing density.…”
Section: Anatomymentioning
confidence: 99%
“…The connectome refers to a comprehensive network description of the brain, often represented as a graph, where nodes denote brain regions and edges represent white matter pathways . Tractography can be used to reconstruct white matter pathways in vivo using diffusion‐weighted MRI (dMRI) . Tractography was originally developed to reconstruct and virtually dissect individual or small groups of white matter fascicles, whereas connectomics requires high‐throughput, whole‐brain reconstruction of thousands of connections.…”
Section: Introductionmentioning
confidence: 99%